Rain call dialects of the Chaffinch Fringilla coelebs in the archipelago of SW Finland - Haartman, L.; Numers, M. (BirdLife Finland, 1992)
In the greater part of Finland, the rain call ofthe male Chaffinch is hüitt, but in the south of the vast SW archipelago of Finland "hüitt" was found to be replaced by "rriip". When c. 80 km of the boundary between these call dialects were mapped, little overlap was found, usually at most a few km. At one site there was a bulge of"hüitt" males into the area of the "rrüp" males. Individuals using the one dialect were only exceptionally heard so deep in the area of the other as to be out of hearing distance ofthe users oftheir own dialect. In an area c. 20 km NE of the continuous range of the "rrüp" dialect, 19 "rrüp" males were recorded during a period of 55 years. They were heard for a few days, but as they were not ringed, it was impossible to decide whether they had stayed and relearnt the call from the surrounding males, or were floaters . "Rrüp" males were also occasionally recorded in other parts of the "hüitt" area in Finland. In part of Karelia and the Leningrad district, a "rrüp" type dialect has long been known to prevail, though detailed information on its boundaries is not available. Factors possibly influencing the development of the archipelago dialect are discussed.